KOHESI GRAMATIKAL PENGACUAN CERPEN KENA BATUNYA KARYA VERONICA PADA BUKU BAHASA INDONESIA SMP KELAS VIII - Muhammad Yunus (STKIP PGRI Banjarmasin, 2021)
ABSTRACT This study aims to describe the grammatical cohesion of references in short stories subjected to veronica's work on Indonesian language books in grade VII. This research is a qualitative study using discourse analysis and describing the grammatical cohesion of references contained in the short story hit by veronica's work on Indonesian language books in grade VII. The results of the research are the grammatical cohesion of persona referencing (me, you, he, he, they, us, me, you, him), Demonstrative referencing (place, time) contained in the short story of Veronica. This research was conducted in order to facilitate the eighth grade junior high school students in distinguishing the grammatical cohesion of references in the short story Kena Batunya Karya Veronica.